Symptoms of depression, perceived social support, and medical coping modes among middle-aged and elderly patients with type 2 diabetes - Zhang, Chuanyan; Wu, Zezhen; Lopez, Elna; Magboo, Romain G.; Hou, Kaijian (Frontiers in Molecular Biosciences, 2023)
Objective: To understand the prevalence of depression in diabetes population, explore the relationship between diabetes and depression, and the impact of comprehensive psychological and behavioral intervention on depression related to diabetes and glucose metabolism. Methods:71 middle-aged and elderly patients with type 2 diabetes were investigated and evaluated with Self Rating Depression Scale (SDS), Medical Coping Scale (MCWQ) and Social Support Scale (PSSS). Patients who met the research criteria were randomly divided into an experimental group and a control group. The number of effective cases in the two groups was 36 and 35 respectively. In addition to conventional diabetes drug treatment, the experimental group was supplemented with comprehensive psychological and behavioral intervention, while the control group was only given conventional treatment. The fasting blood glucose, 2-hour postprandial blood glucose, body weight and depression index were measured before and after treatment in the two groups. Results: The prevalence of depression in patients with diabetes was as high as 60%, and that in the elderly control group was 5%; In type 2 diabetes population, depression is negatively related to the total score of social support and medical coping surface, and positively related to avoidance, blood sugar, women, course of disease, education level below junior high school, body mass index, and number of complications in medical coping; The fasting blood glucose, 2-hour postprandial blood glucose, body mass index, and depression index of the two groups decreased, and the range and speed of decline in the experimental group were higher than those in the control group; There were significant differences between the two groups in fasting blood glucose, 2-hour postprandial blood glucose and depression index; During the follow-up period, the blood glucose and depression index of the experimental group increased. Conclusion:Depression has a high prevalence rate in middle-aged and elderly people with type 2 diabetes, and has a negative impact on blood sugar control in diabetes patients; Psychological and behavioral comprehensive intervention can improve the glucose metabolism and depressive symptoms of middle-aged and elderly patients with type 2 diabetes.